2018
DOI: 10.1177/0950017018809324
|View full text |Cite
|
Sign up to set email alerts
|

Household Employment and the Crisis in Europe

Abstract: The 2008 crisis had a significant impact on household employment in some European countries. An analysis of the EU Statistics on Income and Living Conditions generated a new cross-national typology of household employment structures and showed how these changed during the crisis and austerity period, capturing the experiences of high and low qualified households. Findings indicate that dual earning households are not always a consequence of gender equality but result from economic necessity or employment oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 30 publications
(76 reference statements)
3
40
0
1
Order By: Relevance
“…Comparative research on employment and the family has largely focused on typologies of policy regimes and the identification of dominant types of work–family arrangements (WFA), thereby underestimating within‐country diversity. A few studies have recently shown how these internal differences often reflect variation across socioeconomic groups (Dotti Sani, 2018; Hook, 2015; Sánchez‐Mira & O'Reilly, 2019). However, these studies have often either remained rather descriptive (Dotti Sani, 2018) or have discussed their findings under the frame of the welfare‐regime literature (Hook, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparative research on employment and the family has largely focused on typologies of policy regimes and the identification of dominant types of work–family arrangements (WFA), thereby underestimating within‐country diversity. A few studies have recently shown how these internal differences often reflect variation across socioeconomic groups (Dotti Sani, 2018; Hook, 2015; Sánchez‐Mira & O'Reilly, 2019). However, these studies have often either remained rather descriptive (Dotti Sani, 2018) or have discussed their findings under the frame of the welfare‐regime literature (Hook, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They have thus ignored theoretical discussions on labour market segmentation and institutional dualism that could help advance our understanding of how WFA polarize along social divisions (Dingeldey, 2017; Gottfried, 2013; O'Reilly & Nazio, 2014). Moreover, the mentioned studies have looked at differences by educational attainment (Dotti Sani, 2018; Hook, 2015), arguing that occupational classifications are more directly affected by the idiosyncratic construction of occupational status within countries (Sánchez‐Mira & O'Reilly, 2019). While this is certainly a useful strategy for cross‐national comparisons, using a measure of occupational structure allows for a closer analysis of the effects that segmented labour markets and the regulation of work have on the household organization of labour and how these are rooted in specific historical and societal characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The theoretical contributions of feminist socioeconomics constitute a central reference for understanding and avoiding androcentric views. They will serve to explain the different career paths of men and women (Torns et al 2013;Muñiz-Terra 2020) or the different impact of the crisis according to gender (Rubery 2014;González Gago and Segales Kirzner 2014;Kushi and McManus 2018;Sánchez-Mira and O'Reilly 2018).…”
Section: Inequalities In Work and Family Lifementioning
confidence: 99%